Pengembangan perangkat pembelajaran dengan menggunakan pendekatan keterampilan proses untuk meningkatkan hasil belajar mata pelajaran اجلسمية الرتبية bagi siswa kelas XI IPA MAN I Kota Mojokerto - Sudar Kajin (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Growth and development of the child have the nature of a thorough and intertwined relationships between components (health, nutrition, and environment). In general, child development can be grouped into three areas, namely cognitive, affective, and psychomotor, whereas biological growth which includes a change in the body structure. Body structure regarding the changes in bone structure, especially the long bones that have an impact on changes in body size, whereas changes in bodily functions is a result of hormonal changes that affect the physiological function .. The purpose of this development are: 1) Describe the product feasibility study اجلسمية الرتبية for grade XI IPA at MAN I Mojokerto 2) Describe the development of learning tools using process skills can improve learning outcomes subjects اجلسمية الرتبية class XI IPA at MAN I Mojokerto From the results of this development can be concluded: 1) results of expert validation and testing, the model approach process skills is fit for use for subjects of Physical Education, Sport and Health, because the products developed are not revised by experts but from the results of questionnaire of students stated that require revision are: (a) Improve the look model or change the learning strategy, and (b) improve the use of resources in implementing the model. 2) Product development learning tools using process skills can improve learning outcomes subjects اجلسمية الرتبية class XI IPA at MAN I Mojokerto. From the class of the test increased learning completeness of Pre and Post Tests Tests are respectively 77.78% increase to 91.67%.